Pengaruh Latihan Tactical Attacking Options for Three Players terhadap Menyerang Tim Futsal Putra UNJ - Yosia Melvin Rolandino; Andri Irawan; Abdul Gani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to determine the effect of tactical training on attacking options for three players on the men's futsal team at UNJ. The research method used in this study is a quasi-experimental research design employing a one-group pretest and posttest design. Data collection was conducted at the Achievement Sports Club Futsal FIK UNJ. The population of this study consisted of 80 active members of the Achievement Sports Club Futsal FIK UNJ. The sample selected for this study comprised 17 athletes using proportional sampling technique. The research instrument used in this study employed assessment criteria. Data processing techniques included descriptive statistical analysis and hypothesis testing, showing a calculated t-value. The calculated t-value of 5,49 exceeds the critical t-value of 2.16 at a significance level of α = 0.05. Therefore, it can be concluded that there is a significant effect of tactical training on attacking options for three players on the men's futsal team at UNJ.